Thermal expansion of square from temperature increase of 50K

In summary: Many thanks!It's easily proved.Is there a reason for that?Many thanks!I don't understand why it doesn't change when the quantities are no longer differential.
  • #1
1,169
132
Homework Statement
Pleases see below
Relevant Equations
Please see below
For this problem,
1678218556629.png

The solution is,
1678218601784.png

I understand their logic for their equation, but when I was trying to solve this problem, I came up with a different expression:

##\Delta A = \Delta L_x\Delta L_y##
##\Delta L_x =\Delta L_y = \Delta L## since this is a square.
##\Delta A = \Delta L^2##
##\Delta A = \alpha^2L_i^2\Delta T^2##

I also don't understand how how ##\Delta T = 50K## since it should be converted to celsius since the coefficient of linear expansion is in has unit of inverse celsius.

I did that and got ##\Delta T = -223.15 °C## from ##T_k = T_c + 273.15##

Many thanks!
 
Physics news on Phys.org
  • #2
The Kelvin scale and the Celsius scale have different zero points, but they have the same scale factor. Thus a temperature value of 50°C corresponds to a temperature of 323.15 K, but a temperature difference of 50°C corresponds to a temperature difference of 50 K.

A = L2, but ΔA is not (ΔL)2 but Δ(L2)
i.e. A - Ai = Li2(1+αΔT)2 - Li2
=Li2(2αΔT + α2(ΔT)2)
≈Li22αΔT if αΔT is small.
 
  • Like
Likes ChiralSuperfields and erobz
  • #3
Yes, as @mjc123 points out; take care to write your change in area as follows:

$$(A + \Delta A) - A = ( L+\Delta L )^2 - L^2 $$
 
  • Like
Likes ChiralSuperfields and SammyS
  • #4
Callumnc1 said:
##\Delta A = \Delta L_x\Delta L_y##
##A=L_xL_y.##
The product rule of differentiation is
##dA=L_yd(L_x)+L_xd(L_y)##.
It doesn't change when ##d\rightarrow \Delta.##
 
  • Like
Likes ChiralSuperfields and erobz
  • #5
Callumnc1 said:
I also don't understand how how ##\Delta T = 50K## since it should be converted to celsius since the coefficient of linear expansion is in has unit of inverse celsius.

I did that and got ##\Delta T = -223.15 °C## from ##T_k = T_c + 273.15##

Many thanks!
If ##T_K=T_C+273.15,## it follows that
##\Delta(T_K)=\Delta(T_C)+\Delta(273.15~\text{K}##).
How does 273.15 K change as the temperature of the sheet changes?

It doesn't change because it is a constant. So ##\Delta(T_K)=\Delta(T_C).##
 
Last edited:
  • Like
Likes ChiralSuperfields and FinBurger
  • #6
mjc123 said:
The Kelvin scale and the Celsius scale have different zero points, but they have the same scale factor. Thus a temperature value of 50°C corresponds to a temperature of 323.15 K, but a temperature difference of 50°C corresponds to a temperature difference of 50 K.

A = L2, but ΔA is not (ΔL)2 but Δ(L2)
i.e. A - Ai = Li2(1+αΔT)2 - Li2
=Li2(2αΔT + α2(ΔT)2)
≈Li22αΔT if αΔT is small.
Thank you for your reply @mjc123!

Sorry, where did you get Li2(1+αΔT)2 - Li2 from?

Many thanks!
 
  • #7
erobz said:
Yes, as @mjc123 points out; take care to write your change in area as follows:

$$(A + \Delta A) - A = ( L+\Delta L )^2 - L^2 $$
Thank you for your reply @erobz !

So for the LHS of your expression,
##A_f = A + \Delta A## and ##A_i = A##, correct?

Where ##\Delta A ≠ A_f - A_i##? Sorry I am still getting use to the notation.

Many thanks!
 
  • #8
kuruman said:
##A=L_xL_y.##
The product rule of differentiation is
##dA=L_yd(L_x)+L_xd(L_y)##.
It doesn't change when ##d\rightarrow \Delta.##
Thank you for your reply @kuruman!

Interesting that you use the product rule. Is there a reason for that? Also, why would the area not change as the quantities are no longer differential?

Many thanks!
 
  • #9
kuruman said:
If ##T_K=T_C+273.15,## it follows that
##\Delta(T_K)=\Delta(T_C)+\Delta(273.15~\text{K}##).
How does 273.15 K change as the temperature of the sheet changes?

It doesn't change because it is a constant. So ##\Delta(T_K)=\Delta(T_C).##
Thank you for your reply @kuruman!

That helps to see why the change in temperatures are directly proportional to each other.

However, I am curious why are you allowed to add delta on each side. I have never seen the algebraic operation before (that I am aware of)

Many thanks!
 
  • #10
Callumnc1 said:
Thank you for your reply @kuruman!

That helps to see why the change in temperatures are directly proportional to each other.

However, I am curious why are you allowed to add delta on each side. I have never seen the algebraic operation before (that I am aware of)

Many thanks!
Do you understand what ##\Delta A## symbolizes where ##A## is some quantity?
 
  • Like
Likes ChiralSuperfields
  • #11
Callumnc1 said:
Thank you for your reply @erobz !

So for the LHS of your expression,
##A_f = A + \Delta A## and ##A_i = A##, correct?
Correct
Callumnc1 said:
Where ##\Delta A ≠ A_f - A_i##? Sorry I am still getting use to the notation.
No, that is exactly what it is. How you managed to learn Calculus without understanding this notation is somewhat perplexing…

## A + \Delta A = ( L + \Delta L)^2 ##

If you subtract ##A## ( the area before the change) from both sides you are left with the change in ##A##, i.e. ##( \Delta A)##.

Then ( after expanding the RHS ) if you divide both sides by ##\Delta L## and take the limit as ## \Delta L \to 0## you have the formal method of finding the derivative of ##A## w.r.t. ##L##.
 
Last edited:
  • Like
Likes ChiralSuperfields
  • #12
Callumnc1 said:
Thank you for your reply @kuruman!

That helps to see why the change in temperatures are directly proportional to each other.

However, I am curious why are you allowed to add delta on each side. I have never seen the algebraic operation before (that I am aware of)

Many thanks!
It's easily proved.
##T_{K, initial}= T_{C, initial}+273.15##
##T_{K, final}= T_{C, final}+273.15##
##T_{K, final}=T_{K, initial}+\Delta T_{K}##
etc. You can finish it.
 
  • Like
Likes ChiralSuperfields
  • #13
kuruman said:
Do you understand what ##\Delta A## symbolizes where ##A## is some quantity?
Thank you for your reply @kuruman!

I think ##\Delta A## symbolizes the change in ##A## so ##A_f - A_i##.

Many thanks!
 
  • #14
erobz said:
Correct

No, that is exactly what it is. How you managed to learn Calculus without understanding this notation is somewhat perplexing…

## A + \Delta A = ( L + \Delta L)^2 ##

If you subtract ##A## ( the area before the change) from both sides you are left with the change in ##A##, i.e. ##( \Delta A)##.

Then ( after expanding the RHS ) if you divide both sides by ##\Delta L## and take the limit as ## \Delta L \to 0## you have the formal method of finding the derivative of ##A## w.r.t. ##L##.
Thank you for your reply @erobz!

I am relearning calculus at the moment.

So since ##A = A_f - A_i##, then ##A + \Delta A - A = A + A_f - A_i - A = A_f - A_i = \Delta A##, correct?

Many thanks!
 
  • #15
haruspex said:
It's easily proved.
##T_{K, initial}= T_{C, initial}+273.15##
##T_{K, final}= T_{C, final}+273.15##
##T_{K, final}=T_{K, initial}+\Delta T_{K}##
etc. You can finish it.
Thank you for your reply @haruspex!

I can see how to prove it.

Did you get the third line ##T_{K, final}=T_{K, initial}+\Delta T_{K}## by inspection i.e
##T_{K, final}=T_{K, initial}+ T_{K, final} - T_{K, initial} ##
## 0 = 0 ##

Many thanks!
 
  • #16
Callumnc1 said:
Thank you for your reply @erobz!

I am relearning calculus at the moment.

So since ##A = A_f - A_i##, then ##A + \Delta A - A = A + A_f - A_i - A = A_f - A_i = \Delta A##, correct?

Many thanks!
Yeah, but there is no need to go though all that. You think of the ##\Delta A## as taking a step away from the current value of ##A##, which is the result of taking a step ##\Delta L## away from the current value of ##L##.
 
  • Like
Likes ChiralSuperfields
  • #17
erobz said:
Yeah, but there is no need to go though all that. You think of the ##\Delta A## as a step away from the current value of ##A##.
Thank you for your reply @erobz!

In calculus, isn't ##\Delta A## always positive?

Many thanks!
 
  • #18
Callumnc1 said:
Thank you for your reply @erobz!

In calculus, isn't ##\Delta A## always positive?

Many thanks!

The notation covers steps in either direction.
 
  • Like
Likes ChiralSuperfields
  • #19
erobz said:
The notation covers steps in either direction.
Oh, thank you for your reply @erobz!
 
  • #20
Callumnc1 said:
Oh, thank you for your reply @erobz!
It’s usually written without regard for what direction is the step. It could be a positive value change just as easily as it could be a negative value change. The math handles it no differently…so you usually just see ##+## signs for simplicity. If that is what you are asking about it “always being positive in calculus ”.

If you had in mind that the change is always positive…no.
 
  • Like
Likes ChiralSuperfields
  • #21
erobz said:
It’s usually written without regard for what direction is the step. It could be a positive value change just as easily as it could be a negative value change. The math handles it no differently…so you usually just see ##+## signs for simplicity. If that is what you are asking about it “always being positive in calculus ”.

If you had in mind that the change is always positive…no.
Ah ok. Thank you for help @erobz !
 
  • Like
Likes erobz
  • #22
Callumnc1 said:
I think ##\Delta A## symbolizes the change in ##A## so ##A_f - A_i##.
Right. It is the difference between the final and initial value of the quantity. Now if this quantity is the sum of two quantities, say ##A=B+C##, then a change in ##A## can be due to a change in ##B## or a change in ##C## or a change in both. In the third possibility the change in ##A## would be the sum of the changes in ##B## and ##C##.

A concrete example of this is mechanical energy conservation. Mechanical energy is the sum of kinetic and potential energy, ##ME=KE+PE##. If a block is sliding down a frictionless ramp, both kinetic and potential energy change but their sum (the mechanical energy) does not. The statement ##\Delta (ME)=0## says that mechanical energy is conserved (it doesn't change.) This means that the sum ##KE+PE## also doesn't change although individually both the kinetic and potential energies change. This can only mean that the sum of the changes must be zero, ##\Delta (KE)+\Delta (PE)=0.## Note that if one of the changes is positive, the other has to be negative.

I hope that this example clarifies why ##A=B+C## implies ##\Delta A=\Delta B+\Delta C.##
 
  • #23
kuruman said:
Right. It is the difference between the final and initial value of the quantity. Now if this quantity is the sum of two quantities, say ##A=B+C##, then a change in ##A## can be due to a change in ##B## or a change in ##C## or a change in both. In the third possibility the change in ##A## would be the sum of the changes in ##B## and ##C##.

A concrete example of this is mechanical energy conservation. Mechanical energy is the sum of kinetic and potential energy, ##ME=KE+PE##. If a block is sliding down a frictionless ramp, both kinetic and potential energy change but their sum (the mechanical energy) does not. The statement ##\Delta (ME)=0## says that mechanical energy is conserved (it doesn't change.) This means that the sum ##KE+PE## also doesn't change although individually both the kinetic and potential energies change. This can only mean that the sum of the changes must be zero, ##\Delta (KE)+\Delta (PE)=0.## Note that if one of the changes is positive, the other has to be negative.

I hope that this example clarifies why ##A=B+C## implies ##\Delta A=\Delta B+\Delta C.##
Thank you for your reply @kuruman!

I see now how ##A = B+C## implies ##\Delta A=\Delta B+\Delta C## from that mechanical energy conservation example. So is there really no algebraic operation that allows to apply ##\Delta## to each quantity in an equation, it really just about it logically making sense?

Many thanks!
 
  • #24
Callumnc1 said:
Thank you for your reply @haruspex!

I can see how to prove it.

Did you get the third line ##T_{K, final}=T_{K, initial}+\Delta T_{K}## by inspection i.e
##T_{K, final}=T_{K, initial}+ T_{K, final} - T_{K, initial} ##
## 0 = 0 ##

Many thanks!
No, it continues:
haruspex said:
It's easily proved.
##T_{K, initial}= T_{C, initial}+273.15##
##T_{K, final}= T_{C, final}+273.15##
##T_{K, final}=T_{K, initial}+\Delta T_{K}##
##T_{C, final}=T_{C, initial}+\Delta T_{C}##
##\Delta T_{K}-\Delta T_{C}=(T_{K, final}-T_{K, initial})-(T_{C, final}-T_{C, initial})##
##=273.15-273.15=0##
 
  • #25
haruspex said:
No, it continues:

##T_{C, final}=T_{C, initial}+\Delta T_{C}##
##\Delta T_{K}-\Delta T_{C}=(T_{K, final}-T_{K, initial})-(T_{C, final}-T_{C, initial})##
##=273.15-273.15=0##
Oh ok. Thank you for your help @haruspex !
 
  • #26
Callumnc1 said:
I see now how ##A = B+C## implies ##\Delta A=\Delta B+\Delta C## from that mechanical energy conservation example.
I am not entirely convinced that you do. Both @haruspex and I have addressed your other question
Callumnc1 said:
I also don't understand how how ΔT=50K since it should be converted to celsius since the coefficient of linear expansion is in has unit of inverse celsius.
using different approaches. Can you show how one gets the same result, ##\Delta T_K=\Delta T_C## using each approach?
The @haruspex approach, starting from
##T_{K, initial}= T_{C, initial}+273.15##
##T_{K, final}= T_{C, final}+273.15##
##T_{K, final}=T_{K, initial}+\Delta T_{K}##

The @kuruman approach, starting from
##A=B+C \implies \Delta A=\Delta B+\Delta C##
##T_{K}= T_{C}+273.15.##

Everything that you might need has already been discussed.
 
  • Like
Likes ChiralSuperfields
  • #27
kuruman said:
I am not entirely convinced that you do. Both @haruspex and I have addressed your other question

using different approaches. Can you show how one gets the same result, ##\Delta T_K=\Delta T_C## using each approach?
The @haruspex approach, starting from
##T_{K, initial}= T_{C, initial}+273.15##
##T_{K, final}= T_{C, final}+273.15##
##T_{K, final}=T_{K, initial}+\Delta T_{K}##

The @kuruman approach, starting from
##A=B+C \implies \Delta A=\Delta B+\Delta C##
##T_{K}= T_{C}+273.15.##

Everything that you might need has already been discussed.
Thank you for your reply @kuruman!

Using the @haruspex approach I would solve for 273.15 for the top two equations then set them equal to each other

##T_{K, initial} - T_{C, initial} = T_{K, final} - T_{C, final}##
##T_{K, initial} - T_{K, final} = - T_{C, final} + T_{C, initial}##
##-(T_{K, finial} - T_{K, initial}) = -(T_{C, final} - T_{C, initial}A)##
##-\Delta T_k = -\Delta T_C##
##\Delta T_k = \Delta T_C##

Using the @kuruman approch,
##T_{K}= T_{C}+273.15## implies ##\Delta T_{K} = \Delta T_{C}+ \Delta 273.15##
And since 273.15 is a constant,
##\Delta T_{K} = \Delta T_{C}+ 273.15##
##\Delta T_{K} = \Delta T_{C}## So change in kelvin is proportional to change in Celsius.

Many thanks!
 
  • Like
Likes kuruman
  • #28
Callumnc1 said:
##T_{K}= T_{C}+273.15## implies ##\Delta T_{K} = \Delta T_{C}+ \Delta 273.15##
And since 273.15 is a constant,
##\Delta T_{K} = \Delta T_{C}+ 273.15##
No, since 273.15 is a constant, ##\Delta 273.15=0##, so ##\Delta T_{K} = \Delta T_{C}##.
Callumnc1 said:
##\Delta T_{K} = \Delta T_{C}## So change in kelvin is proportional to change in Celsius.
Not quite. ##\Delta T_{K} = \Delta T_{C}## So change in kelvin is equal to change in Celsius.
 
  • Like
Likes ChiralSuperfields
  • #29
Thank you for your reply @haruspex!

haruspex said:
No, since 273.15 is a constant, ##\Delta 273.15=0##, so ##\Delta T_{K} = \Delta T_{C}##.
Whoops, thank you for mentioning my mistake!
haruspex said:
Not quite. ##\Delta T_{K} = \Delta T_{C}## So change in kelvin is equal to change in Celsius.
True, that is better wording

Many thanks!
 

Suggested for: Thermal expansion of square from temperature increase of 50K

Replies
10
Views
252
Replies
2
Views
987
Replies
1
Views
488
Replies
1
Views
738
Replies
14
Views
378
Replies
7
Views
985
Replies
31
Views
484
Back
Top